DESAIN PIT PENAMBANGAN BATUBARA BLOK C PADA PT. INTIBUANA INDAH SELARAS KABUPATEN NUNUKAN PROVINSI KALIMANTAN UTARA (Jurnal Geomine, 2015)
Design pit is an activity deeping to plot production mines activity by methodic that is utilized is strip mine. To the effect of observational it, to get ideal pit design, with methodics penampang's slicing, coal broadcast, overburden's reserve, coal reserve, geometry bench and stripping ratio. Observational method that is utilized for makings to design pit is program autocad 2012 . There is data even – one data are noticed in makings designs pit covers cant stability( bench's broad, bench high, inclination bevels and coal sediment). Of data processing result, therefore gotten by pit's aperture extent 75.8763 Ha, with stripping ratio point 11: 1 and pit's design coal mining with bench's geometry high which is 7 meters, bench's broad 3 – 4 meters and inclinations 65o. Where is pit's design mining comes up into 2 m at sea level.